2019
DOI: 10.1126/sciadv.aax4899
|View full text |Cite
|
Sign up to set email alerts
|

A defined antigen skin test for the diagnosis of bovine tuberculosis

Abstract: Bovine tuberculosis (bTB) is a major zoonotic disease of cattle that is endemic in much of the world, limiting livestock productivity and representing a global public health threat. Because the standard tuberculin skin test precludes implementation of Bacille Calmette-Guérin (BCG) vaccine–based control programs, we here developed and evaluated a novel peptide-based defined antigen skin test (DST) to diagnose bTB and to differentiate infected from vaccinated animals (DIVA). The results, in laboratory assays and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 38 publications
4
57
0
Order By: Relevance
“…Concerning the use of the ST in solitary, the P22-based STs showed lower Se compared to both the SIT and the SICCT tests, although previous studies in dairy goat flocks, with larger samples and different epidemiological situations, have shown lower Se for SIT (65%, 95% CI: 63.3–68.2) ( 8 ) and SICCT (44.5%, 95% CI: 35–55) ( 42 ). However, the Se of the cP22-ST (74%, 95% CI: 63–83) was similar to Se observed in two previous studies using DIVA STs (based on the peptide cocktails ESAT-6, CFP-10, and Rv3616c) developed for the diagnosis of TB in cattle: 76%, 95% CI: 59–93 ( 43 ) and 75%, 95% CI: 47.7–97.7 ( 44 ). In the latter, the addition of the Rv3020c peptide improved the Se to reach 87.5% (95% CI: 61.7–98.5), being similar to the Se of sP22-ST (87%, 95% CI: 74–94) obtained in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Concerning the use of the ST in solitary, the P22-based STs showed lower Se compared to both the SIT and the SICCT tests, although previous studies in dairy goat flocks, with larger samples and different epidemiological situations, have shown lower Se for SIT (65%, 95% CI: 63.3–68.2) ( 8 ) and SICCT (44.5%, 95% CI: 35–55) ( 42 ). However, the Se of the cP22-ST (74%, 95% CI: 63–83) was similar to Se observed in two previous studies using DIVA STs (based on the peptide cocktails ESAT-6, CFP-10, and Rv3616c) developed for the diagnosis of TB in cattle: 76%, 95% CI: 59–93 ( 43 ) and 75%, 95% CI: 47.7–97.7 ( 44 ). In the latter, the addition of the Rv3020c peptide improved the Se to reach 87.5% (95% CI: 61.7–98.5), being similar to the Se of sP22-ST (87%, 95% CI: 74–94) obtained in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…However, the specificity of DST in BCG-vaccinated animals in skin tests, in bTB endemic settings, was unknown. The results of the current investigation considerably extend the prior observation of specificity of DST in BCG-vaccinated cattle in IGRA by now establishing the specificity of the DST as a skin test reagent in BCG-vaccinated and vaccine naïve calves, which is essential if DST were to be used as a DIVA diagnostic in field settings (16).…”
Section: Discussionsupporting
confidence: 69%
“…We recently developed a synthetic peptide-based DST (representing ESAT-6, CFP-10 and Rv3615c) and demonstrated its considerable sensitivity in reliably detecting M. bovis-infected animals in skin tests and in in vitro assays, while also maintaining high specificity in naïve controls (16). However, the specificity of DST in BCG-vaccinated animals in skin tests, in bTB endemic settings, was unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The World Health Organization (WHO) reported that there were nearly 10.4 million new cases of and 1.7 million deaths caused by TB in 2016, making it one of the most pernicious diseases. [2] Even though tremendous efforts, such as the exploitation of effective drugs [3][4][5] and development of advanced diagnostic methods, [6][7][8][9] have been implemented to combat TB in most countries, the rate of morbidity and mortality have decreased by only 2% and 3% per year, respectively. [2] DOI: 10.1002/adtp.201900189…”
Section: Introductionmentioning
confidence: 99%